PALATAL RUGOSCOPY AS A METHOD OF SEX DETERMINATION IN FORENSIC SCIENCE - Subramanian, Prathusha; Jagannathan, Nithya (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Â  Objective: The role of forensic science in establishing the personal identity is based on DNA analysis, finger print and dental analysis. When the forensic remains are decomposed making all these sources, unavailable palatal rugae served as an important aid as it is resistant to heat and placed deep inside the oral cavity in a secure environment. Thus, palatal rugae can be used as an adjunct in the gender determination. This study was performed to determine the length, number and the patterns of palatal rugae in males and females on right and left side and thereby determine the gender difference. Methods: A total of 50 subjects were included in the study comprising of 25 males and 25 females. An impression of the maxillary arch was made using the hydrocolloid impression material (alginate). The palatal rugae were highlighted using a graphite pencil and the length, number and pattern of the rugae were determined using Thomas and Kotze classification. Statistical analysis was performed to determine the two-tailed significance test to determine the significance between the two genders. Results: The wavy pattern was found to highest, followed by curved, straight, circular and unification pattern. The females showed a statistically significant rise in the unification pattern, whereas males demonstrated higher amount of wavy and straight pattern based on descriptive statistics. There was no statistical difference in the length and number of the rugae in males and females. Conclusion: No two palatal rugae are alike and this forms the basis of rugoscopy. The uniqueness, overall stability and feasibility make palatal rugae an ideal forensic identification marker. Keywords: Rugoscopy, Personal identification, Gender, Marker.